Literature Review: Effect of Interprofessional Collaboration Implementation of Patient Services - Dewi Purnasiwi; Ikhlas M Jenie (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: At present progress in the health, the sector requires health workers to provide professional services. The patient's problem is also increasingly complex. Health workers are required to work in an integrated manner, therefore good collaboration and collaboration between healthcare professionals is needed in realizing patient satisfaction. Health services in hospitals are carried out by various health professionals. Effective interprofessional collaboration practices are key to providing health services. The management of the patient's health and all actions must be patient-focused. The model of providing care with interprofessional collaboration is very important so that all services are coordinated and there is good communication between caregivers. This study aims to find out about the effect of implementing interprofessional collaboration on patients. Methods: This research is a literature review. The research source was taken from several databases, with the keywords "Interprofessional collaboration, patient safety, health services". The Google Scholar database was found in 15,455 journals, EBSCO found 32, NCBI found 98, MEDLINE 23, and ProQuest 61. From the total database, only 11 met the inclusion criteria. Results: This meta-analysis shows that interprofessional collaboration has a positive impact. There are several benefits obtained from the application of interprofessional collaboration, namely affecting patient safety, patient quality of life, reducing the risk of falls, preventing medication errors, increasing the patient's functional status. elderly patients. Conclusion: Interprofessional collaboration or Interprofessional Collaboration (IPC) is collaboration between people with different professional backgrounds and working together to solve patient health problems and realize professional health services that focus on patients.Keywords: health services, interprofessional collaboration (ipc), patient safety